Коготь дракона: [роман] / Ольга Баумгертнер - Баумгертнер Ольга Гартвиновна (Disciples, 2010)
Экземпляры: Аб (20141028) / Инвентарный номер: 101689 / Цена: 100.00 / Авт.знак: Б 29 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6